THE INFLUENCE OF BRAND IMAGE, SERVICE QUALITY AND PERCEIVED PRICE ON CONSUMER PURCHASE INTENTION (CASE STUDY: PT. TIKI JALUR NUGRAHA EKAKURIR (JNE) MANADO) - Terok, Yolanda Laura (Sam Ratulangi University, 2016)
Business in Indonesia is developing rapidly as well as consumers’ demands. The increase of consumers’ demands is a big opportunity for enterprises so they will not waste the chance to offer their products and services to fulfill the increasing demands. Due to the rapid growth of business in Indonesia, service sector also follows the development. The objective of this research is to analyze the influence of brand image, service quality and perceived price on consumer purchase intention of JNE shipping service. The method of analysis used in this research is ordinal regression analysis. The sampling method is simple random sampling and the number of sample of this research is 110 respondents. The results of the analysis are brand image, service quality and perceived price have positive relationship on consumer purchase intention of JNE shipping service. Based on parallel estimates and F test, all independent variables significantly influence the independent variable both simultaneously and partially. JNE should maintain the good relationship with customers and its professional performance to keep the customers’ good perception about the company and also JNE should make the price more compatible with the service and benefits so the purchase intention of consumer will increase.